2014
DOI: 10.1115/1.4026817
|View full text |Cite
|
Sign up to set email alerts
|

Flow in the Simplified Draft Tube of a Francis Turbine Operating at Partial Load—Part I: Simulation of the Vortex Rope

Abstract: Numerical simulations and analysis of the vortex rope formation in a simplified draft tube of a model Francis turbine are carried out in this paper, which is the first part of a two-paper series. The emphasis of this part is on the simulation and investigation of flow using different turbulence closure models. Two part-load operating conditions with same head and different flow rates (91% and 70% of the best efficiency point (BEP) flow rate) are considered. Steady and unsteady simulations are carried out for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…These pressure pulsations may be explained reasonably when a clear distinction between synchronous (axial) and asynchronous (radial) type pressure pulsations is made [7][8][9][10]. [11][12][13]; however, no study has been reported on the investigation of synchronous-and asynchronous-type pressure pulsations in prototypes. Measurements on the model turbines are not completely representative of the prototype and its dynamic behavior [11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%
“…These pressure pulsations may be explained reasonably when a clear distinction between synchronous (axial) and asynchronous (radial) type pressure pulsations is made [7][8][9][10]. [11][12][13]; however, no study has been reported on the investigation of synchronous-and asynchronous-type pressure pulsations in prototypes. Measurements on the model turbines are not completely representative of the prototype and its dynamic behavior [11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 91%
“…13, downward is positive and upward (reverse flow) is negative. As discussed by Foroutan and Yavuzkurt (2014a), the vortex rope forms due to the roll-up of the shear layer at the interface between the low-velocity inner region created by the wake of the crown cone and highly swirling outer flow. This low-velocity inner region (stagnant region) is clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The simulation of a turbulent swirling flow, however, is a challenging task, and accurate numerical calculations of the flow parameters require a careful choice of turbulence closure method. Several previous turbulent swirling flow predictions have been carried out employing the steady Reynolds-averaged NavierStokes (RANS) equations with various turbulence closure models (Yaras and Grosvenor, 2003;Shamami and Birouk, 2008;Foroutan and Yavuzkurt, 2014a). A review of the literature reveals, however, that RANS turbulence models show inadequate performance in simulating highly swirling flows.…”
Section: Introductionmentioning
confidence: 98%
“…This condition may be satisfied in the low-frequency dynamic draft tube surge but not in the wake of the blade [2]. Foroutan and Yavuzkurt [9] studied a simplified draft tube of a model Francis turbine at part load and reported that unsteadiness of the vortex rope cannot be modeled by the URANS approach. Most of the turbulent structures occur in the draft tube for flows in hydro turbines operating at off-design.…”
Section: Introductionmentioning
confidence: 93%